Co‐operative versus non‐co‐operative farmers' weed control decisions in an agricultural landscape. (4th June 2018) - Gonzalez‐Andujar, J L
Summary: This study presents a simple landscape model of the influence of seed dispersal on weed population dynamics between fields. In the model, three fields are interconnected through weed seed dispersal, where seed might move with field equipment, in irrigation water or may be wind‐dispersed. The model is intended to characterise the impact of field‐level weed management decisions on landscape‐level weed population dynamics. Two simple scenarios were studied. The first simulates farmers adopting common effective methods of control on each of the three fields. In the second scenario, farmers manage the weed population independently on each of the three fields. In the first scenario, weed populations were driven to extinction as might be expected with uniformly high levels of weed suppression in each of the three fields. In the second scenario, when the two nearest fields in the sequence experienced control, the weed population was driven to extinction in the second field but not in the first where weed populations were able to survive in spite of high levels of suppression. The results suggest that control measures within a field may not adequately reflect their impact on weed population dynamics when between field seed movement occurs. Another important result is the importance of proximity and spatial arrangement of fields and the resulting influence on weed population dynamics within a field.